PENGEMBANGAN MODEL PROJECT-BASED LEARNING BERBASIS APLIKASI CANVA UNTUK PEMBELAJARAN PKN KELAS 1 SD NEGERI MUNTILAN - Chodariyah, Dwi Enik Nuzul; Sutrisna Wibawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop a Project Based Learning (PjBL) model based on the Canva application for Civic Education (PKN) in Grade 1 of SD Negeri Muntilan. The background of this study is the ineffectiveness of current PKN teaching methods due to a lack of innovation. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The analysis process was conducted to identify the needs and difficulties experienced by students and teachers in PKN learning. The design and development of the model were carried out by integrating the Canva application to enhance students' creativity and participation. The model's implementation was tested in Grade 1 of SD Negeri Muntilan with a sample of 27 students. Evaluation results show that the use of the PjBL model based on the Canva application is effective in improving students' understanding of PKN material, as well as enhancing motivation and active engagement in the learning process. The model also received positive feedback from teachers and students, stating that learning became more interesting and interactive. Thus, the development of the PjBL model based on the Canva application can be an effective alternative to enhance the quality of PKN learning in elementary schools.